Effectiveness of Lazarus’ Multimodal Therapy in Treatment of Burnout Symptoms, Compassion Fatigue and Compassion Satisfaction: A Study on Critical Care Nurses at Kenyatta National Hospital - Murithi, Judith; Mbwayo, Anne; Boyo, Bernard (International Journal of Professional Practice, 2025)
Critical care nurses globally face significant psychological distress due to prolonged trauma exposure, excessive workloads, and limited mental health support. These challenges reduce their ability to sustain Compassion Satisfaction (CS) and manage Burnout Symptoms (BOS) and Compassion Fatigue (CF), contributing to high staff turnover and compromised patient care. This study assessed the effectiveness of Lazarus’ Multimodal Therapy (MMT) in addressing BOS, CF, and CS among nurses at the Critical Care Unit (CCU) of Kenyatta National Hospital (KNH). A randomized controlled trial was conducted with 78 nurses divided into treatment and control groups. A social demographic questionnaire and the Professional Quality of Life Scale (Pro-QOL v5) were used to assess BOS, CF, and CS at baseline, midline, and end line. Only the treatment group received MMT. Analysis using ANOVA at a 95% confidence interval via SPSS 29.0 revealed significant improvements in CS at baseline (p = .003), midline (p = .032), and end line (p = .021); BOS at midline (p = .022) and end line (p = .018); and CF at baseline (p = .012), midline (p = .007), and end line (p = .007). MMT effectively reduced BOS and CF while increasing CS. Participants in the treatment group experienced reduced emotional exhaustion and depersonalization, along with enhanced professional fulfillment. The study concluded that MMT is a highly effective intervention for improving the psychological well-being of critical care nurses. It recommends that healthcare administrators incorporate MMT into wellness programs and training, allocate resources for regular psychological assessments, and that nursing curricula include MMT to foster resilience. Government health agencies should also develop supportive mental health policies to enhance nurses’ well-being and improve healthcare delivery.